This preview shows page 1. Sign up to view the full content.
Unformatted text preview: y=6x-12 and y=x^3-x^2-2x 6(x-2)=x^3-x^2-2x Factor the right side to find where x=0, 6(x-2)=x(x-2)(x+1) We can divide both sides by (x-2) 6=x(x+1) Multiply the right side out and equate the formula to 0 to find where x=0 6=x^2+x 0=x^2+x-6 0=(x-2)(x+3) So 0=x-2 => x=2 tells us that y will intersect at x=2, which was the original point, and 0=x+3 => x=-3 tells us that y will also intersect at x=-3. To get the intersection point, just plug x=-3 back into your original equation to get y: y(-3)=(-3)^3-(-3)^2-2(-3) y(-3)=-27-9+6 y(-3)=-30 So your point is (-3, -30)....
View Full Document
This note was uploaded on 03/24/2011 for the course MATHEMATIC 142 taught by Professor Prof.bruceabgarian during the Spring '11 term at Nassau CC.
- Spring '11